AWS certified advanced networking. (Pragmatic AI Solutions, 2022)
AWS Certified Advanced Networking - Specialty (ANS-C01)-2023 Learning AWS Certified Advanced Networking This video series the AWS Certified Advanced Networking Certification 2023 Lessons Covered Include: 1.0 course intro 1.1 sap prerequisite 1.2 Domain intro 1.3 CDN Pattern 1.4 ELB Design 1.5 Amazon API Gateway 1.6 Route 53 Demo 1.7 Public vs Private Hosted Zones DNS-DEMO 1.8 Load Balancing Layer 3, 4, 7 of OSI Model 1.9 Cloudwatch Metrics Demo 1.1 Layer 1/2 concepts: VLAN, Jumbo Frames 1.11 Multiple AWS Accounts 1.12 VPC Peering 2.0 domain intro 2.1 Infrastructure Automation (IAC) with CDK Demo 2.2 Hybrid Networks 2.3 Authentication and Authorization 2.4 Network Monitoring 2.5 Traffic Management DNS 2.6 AWS Boto3 Cloud9 CodeWhisper Demo 2.7 AWS CLI Demo 3.0 domain intro 3.1 Quotas and Limits in AWS Networking 3.2 Inter-Regional communication patterns 3.3 Network performance testing tools- demo 3.4 VPC Flow logs - Demo 3.5 Different types of Network interfaces AWS 3.6 High-Availability via Route 53 4.0 domain intro 4.1 common security threats 4.2 network acls 4.3 AWS Cloud Trail - Demo 4.4 AWS Trusted Advisor Demo 4.5 Network encryption options AWS 4.6 AWS Shared Security Model 5.0 conclusion Learning Objectives Network Design (25%) Network Implementation (25%) Network Management and Operations (25%) Network Security, Compliance, and Governance Additional Popular Resources Pytest Master Class AWS Solutions Architect Professional Course Github Actions and GitOps in One Hour Video Course Jenkins CI/CD and Github in One Hour Video Course AWS Certified Cloud Practitioner Video Course Advanced Testing with Pytest Video Course AWS Solutions Architect Certification In ONE HOUR Python for DevOps Master Class 2022: CI/CD, Github Actions, Containers, and Microservices MLOPs Foundations: Chapter 2 Walkthrough of Practical MLOps Learn Docker containers in One Hour Video Course Introduction to MLOps Walkthrough AZ-900 (Azure Fundamentals) Quick reference guide 52 Weeks of AWS Episode 8: Infrastructure as Code with CDK and AWS Lambda Learn GCP Cloud Functions in One Hour Video Course Python Devops in TWO HOURS! MLOps Platforms From Zero: DatMLOps Platforms From Zero: Databricks, MLFlow/MLRun/SKLearn AWS Machine Learning Certification In ONE HOUR Fast, documented Machine Learning APIs with FastAPI Zero to One: AWS Lambda with SAM and Python in One Hour AWS Storage Solutions 2022: EBS/S3/EFS/Glacier Python Bootcamp for Data Testing In Python book Minimal Python book Practical MLOps book Python for DevOps-Playlist.